2015
DOI: 10.4187/respcare.03308
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Inhaled Nitric Oxide Protocol Decreases Direct Cost Associated With Its Use

Abstract: BACKGROUND: The objective of this study was to determine whether the implementation of an inhaled nitric oxide protocol (INO) in a pediatric ICU (PICU) would reduce cost associated with its use without negatively affecting patient outcomes. METHODS: This is a retrospective cohort study of 76 subjects who required INO therapy in the PICU during the study period. A nitric oxide setup and weaning protocol was implemented in the PICU. The medical records of subjects who had received INO 18 months after protocol im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Although wide CIs preclude the conclusion that NO has absolutely no clinical benefit among severely hypoxemic patients with ARDS, other evidence argues against its use even in this limited population. Such evidence includes an increased risk of renal dysfunction (6), the high cost of NO (10)(11)(12), and the existence of alternative approaches (prone ventilation [58] and extracorporeal support [67]) that have stronger evidence for clinical benefit. Given the evidence to date, it is highly unlikely that additional randomized trials of NO in severely hypoxemic patients, using different dosing strategies or duration, will be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although wide CIs preclude the conclusion that NO has absolutely no clinical benefit among severely hypoxemic patients with ARDS, other evidence argues against its use even in this limited population. Such evidence includes an increased risk of renal dysfunction (6), the high cost of NO (10)(11)(12), and the existence of alternative approaches (prone ventilation [58] and extracorporeal support [67]) that have stronger evidence for clinical benefit. Given the evidence to date, it is highly unlikely that additional randomized trials of NO in severely hypoxemic patients, using different dosing strategies or duration, will be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of evidence for NO and the high daily cost of USD 1,500-3,000 (10)(11)(12), it continues to be used for approximately 7% of all patients with ARDS ( 13) and for 10% of other mechanically ventilated patients with refractory hypoxemia (14). During the recent HlNl influenza pandemic, NO was administered to a substantial minority of mechanically ventilated patients in academic and community hospitals: 8% in South Korea (15), 12% in Europe (16), and 14% in Canada (17).…”
mentioning
confidence: 99%
“…It is purported that the delivery and monitoring system is the rationale behind the increased price. 44 In terms of iNO, a retrospective cohort study 45 was conducted in a pediatric ICU to determine if the implementation of an iNO protocol would reduce its direct cost without negatively impacting patient outcomes. Overall, the investigators found that the implementation of this protocol, which encompasses both setup and weaning, reduced cost without impacting patient outcomes.…”
Section: Inhaled Vasodilatorsmentioning
confidence: 99%
“…Limiting the ability of care providers to "override" non-critical care medications from automated dispensing cabinets may also be an area of operational control to pursue for medications with rising prices. One extreme measure proposed for low-volume very high-cost medications is to call care providers prior to every dispensed dose to ensure that medication 30,32 Prescribing protocol for an institution developed by a multidisciplinary group across all ICU settings Pharmacist-directed stewardship to enforce prescribing guidelines Use of oral a 2 -agonists to replace continuous-infusion dexmedetomidine Recombinant factor VIIa 37,40 Fixed-dosing protocol for warfarin-induced intracranial hemorrhage Implementation of pharmacist-driven critical bleeding management protocol Inhaled vasodilators 42,[45][46][47][48][49] Protocols regarding setup and weaning Substitution of inhaled prostacyclin Medications with relatively newer price increases Albuterol/ipratropium metered-dose inhaler 53,54 Switch to nebulizer products Minimize all inhaled bronchodilator use Chlorothiazide [56][57][58] Pharmacist stewardship program to enforce prescribing guidelines Substitution of oral adjunctive therapy for diuresis (e.g., metolazone) Nitroprusside [59][60][61] Substitution of nicardipine or clevidipine (branded products but are nonetheless cost saving) Vasopressors 62 Use of midodrine to reduce duration of vasopressor use ICU = intensive care unit.…”
Section: Review Operational Procedures For Drug Acquisition and Prepamentioning
confidence: 99%
“…As a result, it is no surprise that almost two-thirds of units have developed and implemented iNO protocols [16]. To our knowledge, there have been no studies directly evaluating the impact of implementing iNO protocols in neonates, but there is some evidence from the pediatric literature that iNO protocols reduce practice variability, decrease iNO usage and thus lower costs without affecting mortality [73,74]. As such, several local, national and international committees have published evidence-based guidelines to assist NICUs in developing their own institutional protocol.…”
Section: The Role Of Respiratory Care Protocols In Neonatesmentioning
confidence: 99%